CONTENT VALIDITY ANALYSIS OF CHEMICAL ENGINEERING STUDENTS’ NEEDS QUESTIONNAIRES FOR ENGLISH READING MATERIALS DEVELOPMENT - Sri Diana; Rampeng Rampeng (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
This study aimed to evaluate the content validity of English reading material needs questionnaires for chemical engineering students based on critical thinking abilities. The ADDIE model was modified for the Research and Development (R & D) plan that includes this investigation. In the analysis phase, questionnaires are created to define the issue and pinpoint its origin. The questionnaires are divided into three sections. The purpose of the first section is to learn more about the individual identities of the respondents. The second part of the survey tries to find out respondents' levels of proficiency in reading English-language literature as well as their motivations for learning the language. The final section consists of six questions, including how crucial it is to engage in critical thinking activities in order to comprehend English texts, the importance of reading strategies, learning strategies, text types, and the teacher's role. Two experts validate the content of the research tools used for the requirements analysis tests. Gregory's formula is used to assess the expert judgments' data. The results of the study showed that both raters agree with the aspects of personal background, purpose of learning English, students' ability level, Critical thinking activities in understanding English texts, reading techniques, and learning techniques. Both raters also agree on the aspect of 'text types' and 'lecturer's role'. All of the items of the aspects of chemical engineering students' needs questionnaires for English reading materials development are valid and can be distributed without any significant revisions.